2008
DOI: 10.1002/dvg.20432
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic studies of the dark‐like mutant mouse

Abstract: The dark-like (dal) mutant mouse has a pleiotropic phenotype that includes dark dorsal hairs and reproductive degeneration. Their pigmentation phenotype is similar to Attractin (Atrn) mutants, which also develop vacuoles throughout the brain. In further characterizing the testicular degeneration of dal mutant males, we found that they had reduced serum testosterone and developed vacuoles in their testes. Genetic crosses placed dal upstream of the melanocortin 1 receptor (Mc1r) and downstream of agouti, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…To evaluate the physiological effects of Atrn in male reproduction system, we analyzed some reproductive phenotypes between Atrn null mutant mouse Atrn mg-3J and wild-type control males C3HeB/FeJ at different ages. Cota et al found that the testes appeared normal in the 3-month-old Atrn mg-3J , but significant vacuolation was noted in 56% of the 6-month old Atrn mg-3J [17] . In our study, we detected mild vacuolation in the testes of the 5-month-old mutant mice, the similar finding to that of Cota et al At the age of 3 months, the weights of testes and epididymes, the sperm activity and fertility rate revealed no significant differences between the mutant mice and the control ones.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To evaluate the physiological effects of Atrn in male reproduction system, we analyzed some reproductive phenotypes between Atrn null mutant mouse Atrn mg-3J and wild-type control males C3HeB/FeJ at different ages. Cota et al found that the testes appeared normal in the 3-month-old Atrn mg-3J , but significant vacuolation was noted in 56% of the 6-month old Atrn mg-3J [17] . In our study, we detected mild vacuolation in the testes of the 5-month-old mutant mice, the similar finding to that of Cota et al At the age of 3 months, the weights of testes and epididymes, the sperm activity and fertility rate revealed no significant differences between the mutant mice and the control ones.…”
Section: Discussionmentioning
confidence: 96%
“…Research also demonstrated that Atrn mg-3J showed some effects on testicular vacuolation, which was evidenced by adult-onset vacuolation in the seminiferous tubules and interstitial cells [17] . In the present study, we observed the pathological changes of the testes and epididymes of the male Atrn mg-3J mice and their wild-type counterparts, and investigated the testicular enzyme activity as well as the fertility potential of the sperms.…”
mentioning
confidence: 97%
“…The dispersion and aggregation of pigment in zebrafish pigment cells is regulated by signaling through the melanocortin 1 receptor (MC1R), where MC1R activity is required for dispersion (Richardson et al,2008). The pigmentation phenotype of dal mutant mice also involves the MC1R pathway, with their dark coat color representing increased MC1R signaling (Cota et al,2008). The mechanism by which loss of prolidase function causes hyperpigmentation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Mice homozygous for the autosomal recessive dark‐like ( dal ) mutation have a pleiotropic phenotype that includes darkly pigmented fur, small body size, reproductive degeneration, vacuolated cells at the cortical medullary junction of the adrenal gland, mild hydrocephalus, dense bone, and dark‐staining urine (Harris et al,2003; Cota et al,2008). Here, we show that dark‐like ( dal ) mice also develop congenital heart defects that include septal defects and significantly thickened ventricular walls due to cardiomyocyte hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Brain proteins were extracted in MES buffered saline containing 0.1% Triton-X100 and protease inhibitors from animals of the indicated genotypes and ages. Lysates were centrifuged through a discontinuous sucrose gradient as described in ref 40 . and fractions analyzed for the presence of the raft marker flotillin-1 by western blotting.…”
Section: Rml Prions Act Through Mgrn1 and Atrn-independent Pathwaysmentioning
confidence: 99%